2021
DOI: 10.1111/all.15142
|View full text |Cite
|
Sign up to set email alerts
|

Receptor binding domain‐IgG levels correlate with protection in residents facing SARS‐CoV‐2 B.1.1.7 outbreaks

Abstract: Background Limited information exists on nursing home (NH) residents regarding BNT162b2 vaccine efficacy in preventing SARS‐CoV‐2 and severe COVID‐19, and its association with post‐vaccine humoral response. Methods 396 residents from seven NHs suffering a SARS‐CoV‐2 B.1.1.7 (VOC‐α) outbreak at least 14 days after a vaccine campaign were repeatedly tested using SARS‐CoV‐2 real‐time reverse‐transcriptase polymerase chain reaction on nasopharyngeal swab test (RT‐qPCR). SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
(113 reference statements)
0
14
0
Order By: Relevance
“…Among other examples, gaseous and particulate matter (PM) concentrations diminished during the 2020 spring lockdown in forty-four cities in northern China due to reduced human activity and travel restrictions. 4 However, during the same period in the UK, after an initial abrupt reduction, nitrogen dioxide (NO 2 ) increased gradually, suggesting that the early return of vehicles to the road during the lockdown had already offset much of the temporary air-quality improvement. 5 Regarding health impact, the risk of COVID-19 mortality during lockdown diminished alongside major air pollutants in Delhi, India, 6 but not in Mexico City, Mexico, where an inverse relationship was found in the case of fine particulate matter.…”
Section: Lower Induction Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Among other examples, gaseous and particulate matter (PM) concentrations diminished during the 2020 spring lockdown in forty-four cities in northern China due to reduced human activity and travel restrictions. 4 However, during the same period in the UK, after an initial abrupt reduction, nitrogen dioxide (NO 2 ) increased gradually, suggesting that the early return of vehicles to the road during the lockdown had already offset much of the temporary air-quality improvement. 5 Regarding health impact, the risk of COVID-19 mortality during lockdown diminished alongside major air pollutants in Delhi, India, 6 but not in Mexico City, Mexico, where an inverse relationship was found in the case of fine particulate matter.…”
Section: Lower Induction Ofmentioning
confidence: 99%
“…Antibodies directed to RBD are critically important for virus‐neutralization because the RBD‐ACE2 interaction represents the port of entry for the virus into cells leading to its replication in the host and to the consecutive spreading in the population. 3 , 4 The ability of RBD‐specific antibodies to prevent RBD binding to ACE2 can be measured with surrogate molecular interaction assays, 5 which mimic classical virus‐neutralization tests 3 and can therefore be quickly adapted to newly emerging SARS‐CoV‐2 variants of concern by using RBDs from the corresponding virus variants.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Antibodies directed against RBD are important for virus neutralization, 23,24 correlate with protection in vaccinated subjects 25 and due to their ability to prevent the virus from entering the human cell and replicating in the host could be a key for obtaining sterilizing immunity 26 . However, it was found that approximately 20% of COVID‐19 convalescent patients, although producing antibodies to other SARS‐CoV‐2 antigens and epitopes, do not sufficiently produce RBD‐specific IgG antibodies to block the RBD‐ACE2 binding and hence are poor‐ or non‐responders to RBD 23,24 …”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Overall, levels of anti-spike-RBD (receptor-binding domain)-IgG and neutralizing antibodies (which correlate strongly) appear to be good measures of vaccine efficacy. [18][19][20][21] Recent publications report a vaccine efficiency of 80% against infections with the Alpha variant (B.1.1.7), with anti-spike-RBD-IgG titers of 506 BAU/ml or 90% efficacy for titers above 775 BAU/ml. 20,22 Similar studies for the Delta (B.1.617.2) or Omicron (B.…”
Section: Introductionmentioning
confidence: 99%